Peningkatan Pemahaman Salat melalui Pengajaran Terjemahan Bacaan di Desa Toddopulia - Ronny Mahmuddin; Mukran H. Usman (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
STIBA Makassar Real Work Lecture (KKN) Batch VII in Toddopulia Village, Tanralili District, Maros Regency is a real implementation of one of the pillars of the Tri Dharma of Higher Education, namely community service. This research aims to optimize community religious development through various activities designed based on local needs. This research examines the effectiveness of implementing the KKN program in improving the religious and social quality of society. The implementation method begins with mapping community needs using the SOAR Analysis (Strengths, Opportunities, Aspirations, Results) approach, which provides a comprehensive picture of potential, opportunities, aspirations and expected results. Based on this analysis, a relevant work program was prepared, including activities such as Tahsin and Dirosa Teaching programs, Friday Sermons, Imam and Tarwih Lectures, Kindergarten/TPA Teaching, Organizing Funeral Services, Teaching in schools and the Sholeh Children's Festival. The results of this research show success in achieving the main goal of KKN, namely making a significant contribution to religious formation and community empowerment and also strengthening social interactions between students and local residents. The successful implementation of this KKN is proof of the effectiveness of a local needs-based approach in creating a sustainable positive impact.